Critical structure sparing in stereotactic ablative radiotherapy for central lung lesions: helical tomotherapy vs. volumetric modulated arc therapy. - Alexander Chi (PLoS ONE, 2013)
BACKGROUND: Helical tomotherapy (HT) and volumetric modulated arc therapy (VMAT) are both advanced techniques of delivering intensity-modulated radiotherapy (IMRT). Here, we conduct a study to compare HT and partial-arc VMAT in their ability to spare organs at risk (OARs) when stereotactic ablative radiotherapy (SABR) is delivered to treat centrally located early stage non-small-cell lung cancer or lung metastases. METHODS: 12 patients with centrally located lung lesions were randomly chosen. HT, 2 & 8 arc (Smart Arc, Pinnacle v9.0) plans were generated to deliver 70 Gy in 10 fractions to the planning target volume (PTV). Target and OAR dose parameters were compared. Each technique's ability to meet dose constraints was further investigated. RESULTS: HT and VMAT plans generated essentially equivalent PTV coverage and dose conformality indices, while a trend for improved dose homogeneity by increasing from 2 to 8 arcs was observed with VMAT. Increasing the number of arcs with VMAT also led to some improvement in OAR sparing. After normalizing to OAR dose constraints, HT was found to be superior to 2 or 8-arc VMAT for optimal OAR sparing (meeting all the dose constraints) (p = 0.0004). All dose constraints were met in HT plans. Increasing from 2 to 8 arcs could not help achieve optimal OAR sparing for 4 patients. 2/4 of them had 3 immediately adjacent structures. CONCLUSION: HT appears to be superior to VMAT in OAR sparing mainly in cases which require conformal dose avoidance of multiple immediately adjacent OARs. For such cases, increasing the number of arcs in VMAT cannot significantly improve OAR sparing.